Association between interprofessional collaboration readiness and clinical decision making ability of midwifery students - Bulan Kakanita Hermasari; Brian Sahar Afifah; Erindra Budi Cahya (Intelektual Pustaka Media Utama, 2019)
Maternal mortality remains a major challenge to health system worldwide. This problem requires the attention of health practitioners and health professional educators including midwives. Effective clinical decision making is among the most important skills required by healthcare practitioners in the intra-profession and interprofessional context. This study aims to explore the midwifery student's clinical decision-making ability and attitude toward interprofessional learning. This study used quantitative design with cross-sectional approach. Subjects of research were 50 midwifery students. The instruments were The Readiness for Interprofessional Learning Scale (RIPLS) questionnaire; and an assessment rubric of the obstetric case study. Most of the students are not ready to collaborate with other health professions (68%), and have low and moderate clinical decision-making abilities (98%). There is a significant positive correlation (p less than 0.05) between student readiness for interprofessional collaboration with clinical decision-making ability. This study emphasizes that the ability of a midwife in clinical decision making, especially in emergency cases, is related to their readiness or experience in collaborating with other health professionals.